The working group performance modeled by a bi-layer cellular automaton. (February 2016) - Malarz, Krzysztof; Kowalska-Styczeń, Agnieszka; Kułakowski, Krzysztof
The problem of 'humans and work' in a model working group is investigated by means of the cellular automata technique. The attitude of members of a group towards work is measured by an indicator of loyalty to the group (the number of agents who carry out their tasks) and lack of loyalty (the number of agents who give their tasks to other agents). Initially, all agents realize scheduled tasks one by one. Agents with the number of scheduled tasks larger than a given threshold change their strategy to an unloyal one and begin to avoid completing tasks by passing them to their colleagues. Optionally, in some conditions, we allow agents to return to the loyal state; hence the rule is hysteretic. Results are presented on an influence of (i) the density of tasks, (ii) the threshold number of tasks assigned to the agent, forcing him/her to change strategy on the system efficiency. We show that a 'black' scenario of the system stacking in a 'jammed phase' (with all agents preferring the unloyal strategy and having plenty of tasks scheduled for realization) may be avoided when return to loyalty is allowed and either (i) the number of agents chosen for task realization, (ii) the number of assigned tasks, (iii) the threshold value of assigned tasks that forces the agent to conversion from a loyal strategy to an unloyal one, or (iv) the threshold value of tasks assigned to an unloyal agent that forces him/her to task redistribution among his/her neighbors, are smartly chosen.